PRODUCTION OF SYNTHESIS GAS FROM INDONESIAN LOW RANK COALS USING FLUIDIZED BED GASIFICATION REACTOR - SLAMET SUPRAPTO; NURHADI NURHADI (Puslitbang tekMIRA, 2007)
In relation to the objective of securing energy and raw material supplies for industries and increasing of low rank coal utilization; research on the production of synthesis gas from Indonesian coal has been carried out. Low rank coal samples and a fluidized bed reactor which was equipped with gas purification system have been used. The coal samples used were Adaro coal (sub bituminous), Mulia and Gunung Bayan (lignitic coals). Gasifying agent was also varied and consisted of oxygen, oxygen/ steam mixture and steam. Stoichiometric ratio of oxygen/carbon was kept at one half and oxygen/ steam ratio was one. The gasification temperature was kept constant at 900ºC. The composition of gas products were analyzed using a gas chromatograph with molsieve and porapak columns. The results showed that there was a good correlation between gasifying agent, coal used, quality and quantity of synthesis gas.